Analisis Yuridis Pemblokiran Sertifikat Tanah Ditinjau Dari Peraturan Menteri Agraria Dan Tata Ruang/Kepala Badan Pertanahan Nasional - Rizki, Mohd. Arif; Purba, Hasim; Sutiarnoto, Sutiarnoto; Agustining, Agustining (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
This article aims to present a study of Indonesian law regarding ownership of land rights. The research was carried out using the library research method, namely document study, by collecting and studying legal books, literature, scientific writings, statutory regulations, and other readings related to the writing of this thesis, and the documents studied were decisions decision in court. Data analysis in this research was carried out qualitatively; that is, the data obtained was then compiled systematically and then analyzed qualitatively to achieve clarity on the problems discussed. This research is descriptive and analytical, revealing statutory regulations related to legal theories that are the object of research, as well as the implementation of these laws in society. The data analysis method is used to produce analytical descriptive data, namely what respondents express in writing or orally and also their real behavior, as researched and studied as a whole. The results of the research explain that legal protection against certificate blocking consists of two forms, namely preventive in the form of prevention and repressive in the form of resolution through the courts. The legal extension of blocking a certificate holder is that the certificate holder cannot take legal action in the form of recording or registering confiscations, while the legal consequence of blocking a certificate is that data maintenance and land registration activities cannot be carried out.